Gad1 knock-out rats exhibit abundant spike-wave discharges in EEG, exacerbated with valproate treatment - Liu, Dongyu; Fujihara, Kazuyuki; Yanagawa, Yuchio; Mushiake, Hajime; Ohshiro, Tomokazu (Frontiers in Neurology, 2023)
Objective To elucidate the functional role of gamma-aminobutyric acid (GABA)-ergic inhibition in suppressing epileptic brain activities such as spike-wave discharge (SWD), we recorded electroencephalogram (EEG) in knockout rats for Glutamate decarboxylase 1 (Gad1), which encodes one of the two GABA-synthesizing enzymes in mammals. We also examined how anti-epileptic drug valproate (VPA) acts on the SWDs present in Gad1 rats and affects GABA synthesis in the reticular thalamic nucleus (RTN), which is known to play an essential role in suppressing SWD. Methods Chronic EEG recordings were performed in freely moving control rats and homozygous knockout Gad1 (–/–) rats. Buzzer tones (82 dB) were delivered to the rats during EEG monitoring to test whether acoustic stimulation could interrupt ongoing SWDs. VPA was administered orally to the rats, and the change in the number of SWDs was examined. The distribution of GABA in the RTN was examined immunohistochemically. Results SWDs were abundant in EEG from Gad1 (–/–) rats as young as 2 months old. Although SWDs were universally detected in older rats irrespective of their Gad1 genotype, SWD symptom was most severe in Gad1 (–/–) rats. Acoustic stimulation readily interrupted ongoing SWDs irrespective of the Gad1 genotype, whereas SWDs were more resistant to interruption in Gad1 (–/–) rats. VPA treatment alleviated SWD symptoms in control rats, however, counterintuitively exacerbated the symptoms in Gad1 (–/–) rats. The immunohistochemistry results indicated that GABA immunoreactivity was significantly reduced in the somata of RTN neurons in Gad1 (–/–) rats but not in their axons targeting the thalamus. VPA treatment greatly increased GABA immunoreactivity in the RTN neurons of Gad1 (–/–) rats, which is likely due to the intact GAD2, another GAD isozyme, in these neurons. Discussion Our results revealed two opposing roles of GABA in SWD generation: suppression and enhancement of SWD. To account for these contradictory roles, we propose a model in which GABA produced by GAD1 in the RTN neuronal somata is released extrasynaptically and mediates intra-RTN inhibition.